Pemikiran Al-Farabi dalam Pendidikan dan Relevansinya terhadap Perancangan Kurikulum - Mukti Peni Indrawati; Kiky Fatmawati; Muhishah Hidayati; Sumarno (Al-Kindi, 2026)
This study reconstructs the core of Al-Farabi’s educational thought and demonstrates its relevance to the design of curriculum, pedagogy, and governance of contemporary Islamic educational institutions. Through a literature review using a descriptive analytical method, the study examines the epistemological framework (the stages of sense perception, intellect, and acquired intellect atauʿaql mustafad, the classification of knowledge as the architecture of the curriculum, the roles and competencies of teachers, learning strategies, and the teleological goal of education saʿādah which is intrinsically connected to socio-political order. The findings affirm that: (1) education from Al-Farabi’s perspective is integrative, synergizing rationality, moral character, and spirituality (2) an ideal curriculum integrates religious sciences, logic, science, and the arts to cultivate critical thinking, creativity, and ethical leadership (3) teachers are positioned as intellectual-moral exemplars who combine demonstrative argumentation with pedagogical discipline in accordance with learners’ readiness and (4) the ultimate aim of education is the perfection of intellect and character, manifested in public welfare. Thus, Al-Farabi’s thought provides a robust theoretical foundation for the renewal of Islamic education that is both competitive and civilizationally grounded.